2019
DOI: 10.3171/2017.12.jns172423
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postoperative motor function in rolandic meningiomas

Abstract: OBJECTIVEResection of supratentorial meningiomas is generally considered a low-risk procedure, but tumors involving the rolandic cortex present a unique challenge. The rate of motor function deterioration associated with resecting such tumors is not well described in the literature. Thus, the authors sought to report the rates and predictors of postoperative motor deficit following the resection of rolandic meningiomas to assist with patient counseling and surgical de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…Progressive paresis as an admitting symptom beside disturbing the IOM is considered to be a negative prognostic factor for the motor outcome (47,2 % vs 22,2%, p = 0,017, Ottenhausen et al, 2018) [26]. In our group of patients in one case we had aggravation of the pre-existent deficit and new deficit was observed in 10,52% of the cases.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Progressive paresis as an admitting symptom beside disturbing the IOM is considered to be a negative prognostic factor for the motor outcome (47,2 % vs 22,2%, p = 0,017, Ottenhausen et al, 2018) [26]. In our group of patients in one case we had aggravation of the pre-existent deficit and new deficit was observed in 10,52% of the cases.…”
Section: Discussionmentioning
confidence: 51%
“…Ottenhausen et al, found that a high rate of neurological deficit was associated with parafalcine insertion, large tumoral mass and perilesional oedema. Another negative prognostic factor was found to be the necessity for preoperative embolization and the involvement of the Rolandic drainage vein [26]. From our group of patients in one case it was necessary to perform an endovascular procedure, tumour's location being on the falx cerebri to facilitate the resection.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The multivariate analysis was performed by Logistic regression model. Potential-risk estimators with P value <0.05 in the univariate Logistic regression analysis or based on clinical importance, scientific knowledge and predictors identified in previously published articles (7,10,(26)(27)(28)(29), among all variables, were tested in the multivariate model. Backward stepwise selection with the Akaike information criterion (AIC) was used to identify variables for the multivariable Logistic regression model and Odd ratios (ORs) were presented with their 95% confidence intervals (CIs).…”
Section: Comparison Of Clinical Featuresmentioning
confidence: 99%